Two Sides of a Coin: A Grief Memoir and its Readers. Issue 4 (2nd October 2022) - Bartlett, R. Allana; Den Elzen, Katrin; Moniz, Tracy; Rehberg Sedo, DeNel
ABSTRACT: This interdisciplinary study represents a scholarly examination of a grief memoir text and its readership. This duality matters because it begins to address a gap in research that sees textual analysis and narrative theory on the one hand, and reading studies on the other almost always investigated independently. Our work examines Becky Aikman's (2013) representation of grief, fractured identity, and the role of friendship in rebuilding the self in her grief memoir, Saturday Night Widows: The Adventures of Six Friends Remaking Their Lives . The literature on memoir generally and grief memoir specifically positions autobiographical writing as a performative act to bring narrative coherence to a life disrupted. The Goodreads reviews we analyse as readers' responses to Aikman's book demonstrate that readers do not approach this grief memoir with the same sense-making drive as did its author. The surprising findings render visible the assumptions we make of nonprofessional memoir readers' motivations and engagement. Expanding our understanding of the role of grief memoir in the grief process calls for further study of both writers and readers of the genre.